The Selection and Contextual Use of Hadith in Khutbah: A Comparative Study between Indonesia and Malaysia - Abdul Majid; Latifah Abdul Majid; Sitti Sagirah; Muhaemin Muhaemin (Borneo International Journal of Islamic Studies, 2025)
Khutbah is a lecture or speech delivered by a Khatib before Friday prayers, which is one form of Islamic preaching. The Khutbah material delivered by the Khatib typically responds to or addresses issues that are currently being discussed. This paper aims to examine the hadith in the Khutbah material delivered by Indonesian and Malaysian Khatib in responding to issues that are presently discussed. This research employs a qualitative comparative study model. The results of the study show that the hadith quoted by Khatib in Khutbah material in Indonesia and Malaysia vary, due to differences in issues. However, in general, the themes raised are similar, primarily concerning politics, socio-humanity, the environment, violence in the name of religion, and tolerance. This study also found differences in the freedom of preachers in the two countries. Servants in Indonesia have the freedom to create their own Khutbah scripts, while Malaysian Khatib must follow the official government script.